Tough Adhesive Hydrogel for Intraoral Adhesion and Drug Delivery. (May 2023) - Wu, D.T.; Freedman, B.R.; Vining, K.H.; Cuylear, D.L.; Guastaldi, F.P.S.; Levin, Y.; Mooney, D.J.
Oral lichen planus (OLP) and recurrent aphthous stomatitis (RAS) are common chronic inflammatory conditions, manifesting as painful oral lesions that negatively affect patients' quality of life. Current treatment approaches are mainly palliative and often ineffective due to inadequate contact time of the therapeutic agent with the lesions. Here, we developed the Dental Tough Adhesive (DenTAl), a bioinspired adhesive patch with robust mechanical properties, capable of strong adhesion against diverse wet and dynamically moving intraoral tissues, and extended drug delivery of clobetasol-17-propionate, a first-line drug for treating OLP and RAS. DenTAl was found to have superior physical and adhesive properties compared to existing oral technologies, with 2 to 100× adhesion to porcine keratinized gingiva and 3 to 15× stretchability. Clobetasol-17-propionate incorporated into the DenTAl was released in a tunable sustained manner for at least 3 wk and demonstrated immunomodulatory capabilities in vitro, evidenced by reductions in several cytokines, including TNF-α, IL-6, IL-10, MCP-5, MIP-2, and TIMP-1. Our findings suggest that DenTAl may be a promising device for intraoral delivery of small-molecule drugs applicable to the management of painful oral lesions associated with chronic inflammatory conditions.